Systematic Review on Health Law in Indonesia During the COVID-19 Pandemic - Rif'atul Hidayat (Jurnal KESANS : Kesehatan dan Sains, 2022)
Studying health law issues from previous studies may open new opportunities to find more varied research and get updates. It is necessary to analyze previous research by conducting a Systematic Review in the field of Health law during COVID-19. To conduct a literature review or Systematic Review of research from   various international journals from 2020-2021. Bibliometric analysis method consisted of defining search keywords, namely Health Law in Indonesia During the COVID-19 Pandemic, (2.) search results preliminary data, (3.) narrowing of search results, (4.) compilation of preliminary data statistics, and (5.) data analysis. The findings of the study were 247 articles from 13 publishers, the most published articles related to auditing were published by publishing institution named 'Elsevier '. The most published articles in 2021 were 170 articles. Meanwhile, the most cited article citations in 2020 were 638 citations with the title Review and analysis of current responses to COVID-19 in Indonesia: Period of January to March 2020